A numerical model for second harmonic ion cyclotron heating of sloshing ions in mirror trap - Moiseenko, V.E.; Ågren, O. (Вопросы атомной науки и техники, 2006)
A numerical model calculating the distribution of radio-frequency fields and absorption of their energy by sloshing
ions is presented. The model solves time-harmonic Maxwell’s equations written in terms of the electric field and
accounts for fundamental and second harmonic ion cyclotron wave damping. It uses a 2D grid, Fourier series in the 3rd
coordinate and is based on a non-staggered mesh not aligned along the steady magnetic field. Numerical stability of the
scheme is demonstrated, and the convergence analysis is presented. Представлена численная модель для расчета распределения электромагнитных полей и поглощения энергии
плещущимися ионами. В рамках модели решаются уравнения Максвелла для электрического поля при учете
ионно-циклотронного поглощения на первой и второй гармониках. Она использует двумерную сетку и
разложение Фурье по третьей координате и базируется на не качающейся, не связанной с направлением
магнитного поля сетке. Обеспечена численная устойчивость этой схемы и приведен анализ сходимости. Подана числова модель для розрахунку розподілу електромагнітних полів та поглинання енергії іонами, що
плескаються. В рамках моделі розв’язуються рівняння Максвела для електричного поля з урахуванням іонно-
циклотронного поглинання на першій та другій гармоніках. Вона використовує двовимірну сітку і розлад Фур’є
по третій координаті та базується на сітці, що не пов’язана з напрямком магнітного поля та не гойдається.
Забезпечено числову стійкість цієї схеми та наведений аналіз збіжності.